Influence of sewage water on the water quality of Diyala River in Baqubah City - Khwedim, Kareem (Iraqi Journal of Science, 2024)
(10) Water samples were collected from Diyala River within Baqubah City, inaddition to two water samples, one sample from Diyala River before Baqubah cityand the other one after the city. (4) Sewage water samples were collected to the influence of sewage water on the quality of Diyala River which is dischargeddirectly to the river without treatment, sampling campaign achieved in February /2011. Chemical analysis were conducted to measure the concentrations of majorcontents & trace elements (Pb, Cd, Zn, Cu & Ni) to estimate the environmentalsituation for Diyala River and its uses for different purposes. The results revealedthat the water samples have high concentration of some major contents especially(Mg & Ca) whereas the sewage water has high concentrations of (K, SO4 & Ca)according to the drinking water criteria of (WHO),Sodium Adsorption Ratio (SAR) in the water samples was less than (10) & it’ssuitable to use as irrigation water according to their Sodium content while the meanof total hardness (TH) was above the international limits according to the drinkingwater criteria of (WHO) and Iraqi limits, therefore it’s classified as hard water,Water type for the most water samples was (Ca- Mg- SO4 – Cl – Bicarbonate). Thecomparison with drinking water criteria was done to see the possibility of using thewater of Diyala River as drinking water as well as the obtained results comparedwith animal’s drinking water criteria and with the irrigation water criteria.Some trace elements (Pb, Cd, Zn, Cu & Ni) were chosen to measure their levels inDiyala River; the concentrations of (Pb, Cd & Ni) were above the internationallimits according to the drinking water criteria of (WHO) whereas (Zn & Cu) wereunder these limits, the increasing in the concentrations of some trace elements is dueto the sewage water & domestic waste which discharge directly to the Diyala Riverwithout treatment.